2021
DOI: 10.1503/jpn.200238
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of cellular aging markers in obsessive–compulsive disorder: mitochondrial DNA copy number and telomere length

Abstract: Background: The present study examined whether mitochondrial DNA copy number (mtDNAcn) and telomere length — key markers of cellular aging — were altered in male and female participants with obsessive–compulsive disorder (OCD) compared to healthy controls. We also tested for associations between these alterations and OCD-related clinical features and inflammatory index. Methods: A total of 235 patients with OCD (38.7% female) and 234 healthy controls (41.5% female) were included. We quantified whole-blood mtD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Mitochondria was principal hub in the regulation of immune and inflammatory responses [ 32 ]. A population-based study for obsessive-compulsive disorder, which was a chronic neuropsychiatric disorder, has reported that the disorder and an increased NLR were associated with mtDNAcn, rather than with LTL [ 33 ]. Furthermore, it has been suggested that inflammatory stress causes an increased reactive oxygen species production and accumulated mtDNA damage, and the interaction between oxidative stress and mitochondrial dysfunction can result in energetic failure and death, biological aging, and the pathogenesis of age-related diseases [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria was principal hub in the regulation of immune and inflammatory responses [ 32 ]. A population-based study for obsessive-compulsive disorder, which was a chronic neuropsychiatric disorder, has reported that the disorder and an increased NLR were associated with mtDNAcn, rather than with LTL [ 33 ]. Furthermore, it has been suggested that inflammatory stress causes an increased reactive oxygen species production and accumulated mtDNA damage, and the interaction between oxidative stress and mitochondrial dysfunction can result in energetic failure and death, biological aging, and the pathogenesis of age-related diseases [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results were replicated in a tandem (combined) analysis of the telomere content and leukocyte mtDNA copies in young and middle-aged individuals [43,44]. More significant correlation was observed in groups of patients with signs of psychiatric or developmental disorders [45].…”
Section: Non-inclusion Criteriamentioning
confidence: 66%
“…Controversial data 2 on telomere length in schizophrenia relative to healthy controls has been reported in the literature, but the results of meta-analyses [ 19 , 41 ] demonstrate a significant telomer shortening in young patients with schizophrenia spectrum disorders [ 42 ]. These results were replicated in a tandem (combined) analysis of the telomere content and leukocyte mtDNA copies in young and middle-aged individuals [ 43 , 44 ]. More significant correlation was observed in groups of patients with signs of psychiatric or developmental disorders [ 45 ].…”
Section: Introductionmentioning
confidence: 82%
“…Previous observational studies have given little attention to OCD in older adults. Some studies suggest that individuals with OCD experience accelerated brain aging, as well as shortening of mitochondrial DNA copy number (mtDNAcn) and telomere length in the blood ( 44 , 45 ). However, our study did not observe a bidirectional relationship between FI and OCD.…”
Section: Discussionmentioning
confidence: 99%